Case report: A rare case of eosinophilic cholecystitis presenting after talc pleurodesis for recurrent pneumothorax. (2017) - Caesar, J.; Jordan, M.; Hills, M.
Abstract: Eosinophilic cholecystitis (EC) is a rare inflammatory condition of the gallbladder, confirmed by a cellular infiltrate comprised of more than 90% eosinophils in the gallbladder wall on histological examination. Although the etiology of EC is largely unknown, local autoimmune reactions within the gallbladder wall to inflammatory mediators from distal sites of inflammation have been hypothesized. Talc pleurodesis (TP) is a common clinical procedure used within respiratory medicine. However, it is associated with activation of systemic acute inflammatory responses including an increase in serum interleukin-8 (IL-8), which is a potent mediator of eosinophil chemotaxis. We report a case of EC following a TP procedure for persistent, secondary pneumothorax.